Quality Analysis Of Library Information System Using Webqual Toward User Satisfaction - Dwi Januarita; Fauzan Romadlon (JURNAL INFOTEL, 2018)
Websites for educational institutions is a form of information services that can be accessed online. One of the information services in educational institutions is library information system. This research focused on Institut Teknologi Telkom Purwokerto as an object of library information system implementation (dlibrary). Corresponding with the library strategy to become "user-friendly", the library of Institut Teknologi Telkom Purwokerto has provided information that follows user requirements and understanding. The one of user satisfaction for accessing the "dlibrary" is the provided quality information system. This research uses Webqual Method. Webqual method is a method for measuring the quality of information from web. This research is done by taking the perspective of the users about the information quality of the website. The 95% confidence level is used in this research, and the result on the dimensions of information quality (usability quality, information quality, and service interaction quality) has significant influence against the user satisfaction. It indicates that the content of the "dlibrary" information are accurate, complete, understandable, relevant and present information in accordance with the needs of the user.